Musicality and functions of Mandolin Gamelans in Pupuan Tabanan Village - Mawan, I Gede; Rai S, I Wayan; Sudirga, I Komang; Suharta, I Wayan (International research journal of management, IT and social sciences, 2023)
Gamelan Mandolin is a traditional music in Pupuan Village, Tabanan whose existence is still maintained today. Gamelan Mandolin as part of Balinese karawitan, is very rich in musical elements. The richness of his musical elements can be seen from the form and type of repertoire, composition, rhythm, melodic formula, and patterns he works on. Apart from containing elements of musicality, Gamelan Mandolin in Pupuan Village has a close correlation with the function of art in people's lives. Its existence is indispensable in community life which can be functioned in various patterns of social activities. In its development in society, Gamelan Mandolin has several functions, both primary and secondary functions. This paper discusses the musicality and function of the Mandolian Gamelan in the social life of the Pupuan people. The method used is a qualitative method by describing the musicality and function of Gamelan Mandoli in the social life of the community.